Effects of total parenteral nutrition and enteral fluid therapy, with or without glutamine, and crystalloid fluid therapy on the renal function of horses subjected to starvation after exploratory laparotomy - Melo, Ubiratan; Palhares, Maristela Silveira; Leme, Fabiola Oliveira Paes; Ferreira, Cintia; Gheller, Valentim Arabicano; Maranhão, Renata de Pino Albuquerque (Revista de Ciências Agroveterinárias, 2025)
In clinical practice, variable periods of food restriction, partial or total, are common due to illnesses or the performance of diagnostic and/or surgical procedures, or after surgical procedures to prevent complications, such as postoperative colic. To assess the effect of total parenteral nutrition associated with glutamine and enteral fluid therapy, with or without glutamine, on the renal function of horses subjected to starvation after exploratory laparotomy (phase 1) and refeeding (phase 2), 16 healthy adult mixed-breed horses aged between four and 14 years and weighing on average 248.40±2.28 kg were used, divided into four experimental groups (n=4): Group I (ENTGL): enteral fluid therapy with electrolytes associated with glutamine; Group II (PARGL): total parenteral nutrition associated with glutamine; Group III (ENTFL): enteral fluid therapy with electrolytes; and Group IV (PARFL): parenteral fluid therapy. This study was divided into two phases. Phase 1 involved exploratory laparotomy and the initiation of starvation, along with the administration of treatments according to the group, while phase 2 involved refeeding the animals. There was a progressive increase in urinary protein concentration, especially in the PARGL group. Glycosuria was observed in the PARGL, ENTGL, and PARFL groups. Aciduria was observed only in the PARGL group. A decrease in creatinine clearance and GGT was observed throughout the first experimental phase, considering the overall mean of the times, with heterogeneous behavior of variables within the groups.